Pathophysiological changes in inner hair cell ribbon synapses in the ageing mammalian cochlea - Jeng, Jing-Yi (J Physiol, 2020)
Mammalian cochlear inner hair cells (IHCs) are specialized sensory receptors able to provide dynamic coding of sound signals. This ability is largely conferred by their ribbon synapses, which tether a large number of vesicles at the IHC’s presynaptic active zones, allowing high rates of sustained synaptic transmission onto the afferent fibres. How the physiological and morphological properties of ribbon synapses change with age is still largely unknown. Here, we have investigated the biophysical and morphological properties of IHC ribbon synapses in the ageing cochlea (9-12 kHz region) of four mouse strains commonly used in hearing research: early-onset progressive hearing loss (C57BL/6J and C57BL/6NTac) and “good hearing” strains (C57BL/6NTac(Cdh23+) and C3H/HeJ). We found that with age, both modiolar and pillar sides of the IHC exhibited a loss of ribbons, but an increased volume of those that remained. These morphological changes, which only occurred after 6 months of age, were correlated with the level of hearing loss in the different mouse strains, being most severe for C57BL/6NTac and C57BL/6J, less so for C57BL/6NTac(Cdh23+) and absent in C3H/HeJ strains. Despite the age-related reduction in ribbon number in three out of four strains, the size and kinetics of Ca(2+)-dependent exocytosis, as well as the replenishment of synaptic vesicles, in IHCs was not affected. The degree of vesicle release at the fewer, but larger, individual remaining ribbon synapses colocalized with the post-synaptic afferent terminals is likely to increase, indicating the presence of a previously unknown degree of functional compensation in the ageing mouse cochlea. ABBREVIATIONS: